Transformation of Courtyards in the Historic Core of Kathmandu: Typologies, Functions, and Socio-Economic Shifts - Shrestha, Astha; Vaidya, Prizma; Bhattarai, Rheecha; Parajuli, Rijan; Phuyal, Subash (KEC Journal of Science and Engineering, 2026)
Courtyards have been at the heart of Kathmandu’s spatial, social and spiritual life. This paper examines how these traditional spaces- once integral to the collective identity, religious practice, and urban ecology are changing under the forces of modernization, migration and economic transformation. Based on the case studies of three historic bahals: ItumBahal, Shree Gha Bahal and TeBahal the research examines changes in typology, function and meaning. Using participants observation, semi-structured interviews, and site documentation, the research illustrates how some courtyards remain strong communal and religious spaces, while others are being degraded or commercialized. The research identifies the need for reconciliation between heritage conservation and evolving urban conditions.